Pole piece, secondary battery and electric equipment

By introducing a polymer layer of heat-shrinkable material into the composite fluid-collection structure of the lithium-ion battery electrode sheet, the metal layer recesses are formed to connect the electrode ears, the problem of insufficient welding strength in the prior art is solved, and higher welding firmness and electron conduction efficiency are achieved.

CN222720443UActive Publication Date: 2025-04-04ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202421136046.1
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-05-21
Publication Date
2025-04-04
Estimated Expiration
2034-05-21

AI Technical Summary

Technical Problem

The sandwich structure of the existing lithium-ion battery electrode sheet is prone to cracking and insufficient welding strength when welding the electrode ears, which limits the production and use of electrode sheets.

Method used

A composite fluid collector structure is adopted, wherein the polymer layer includes a heat-shrinkable material portion, which is thinned relative to the initial thickness at the welding position, forming a metal layer depression, and the pole ears are connected to the depression, thereby improving the welding strength and electron conduction rate.

Benefits of technology

The welding firmness of the electrode sheet on the current collector is significantly improved, the strength of the welded electrode and the electron conduction efficiency are ensured, while the thickness of the battery cell is reduced and the flatness is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222720443U_ABST
    Figure CN222720443U_ABST
Patent Text Reader

Abstract

The utility model discloses a pole piece, a secondary battery and electric equipment. The pole piece comprises a current collector and a pole lug, the current collector comprises a first metal layer, a second metal layer and a polymer layer located between the first metal layer and the second metal layer, the polymer layer comprises a thermal shrinkage material part, and the thermal shrinkage material part has a first thickness and a second thickness which is thinned relative to the first thickness at a set position; the first metal layer and / or the second metal layer inwards form a recess at a set position; the tab is connected to the recess. According to the pole piece provided by the embodiment of the invention, the middle layer on the current collector is reduced and thinned in the position of the tab joint to form the recess, so that the metal layer of the composite current collector can be welded with the tab during connection, particularly welding, the strength of the welded tab can be ensured, the conduction rate of electrons on the metal layer can also be ensured, and the performance of the pole piece is improved. And meanwhile, the tabs generate a structure similar to'embedding 'of the tabs on the pole pieces, so that the overall thickness of the battery cell can be effectively reduced, and the flatness of the battery cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to pole pieces, secondary batteries and electrical equipment. Background Art

[0002] Lithium-ion batteries have been widely used in digital products and power supplies. Among them, high-safety, high-specific energy, and low-cost lithium-ion batteries are the main development direction of battery technology. This has led to the development of new current collectors, and pole pieces with polymer materials with good insulation, low density, and low cost as the intermediate layer have come into being. The pole piece uses polymer materials as the intermediate layer base film and is plated with aluminum / copper conductive layers on both sides. It is a sandwich-like structure. However, it is this sandwich structure that causes many problems such as broken welds when connecting Al / Ni pole ears. The firmness of the welding needs to be improved, which seriously limits the actual production and use of pole pieces. Utility Model Content

[0003] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application provides a pole piece, a secondary battery and an electric device, wherein the firmness of welding the pole ear of the pole piece on the current collector is greatly increased.

[0004] In a first aspect of the present application, a pole piece is provided, the pole piece comprising:

[0005] A current collector, comprising a first metal layer, a second metal layer and a polymer layer located between the first metal layer and the second metal layer, wherein the polymer layer comprises a heat shrinkable material portion, the heat shrinkable material portion has a first thickness and a second thickness that is thinner than the first thickness at a set position, and the first metal layer and / or the second metal layer is recessed inwardly at the set position;

[0006] The tab is connected to the depression.

[0007] The pole piece according to the first aspect of the present application has the following beneficial effects:

[0008] The pole piece makes the middle layer on the current collector thinner at the position of connecting the pole ear so that the metal layer forms a depression, so that the metal layer of the composite current collector can be welded together with the pole ear during connection, especially welding, which can ensure the strength of the welded pole ear and the conduction rate of electrons on the metal layer. At the same time, the pole ear produces a structure similar to the "embedded" pole ear on the pole piece, which can effectively reduce the overall thickness of the battery cell and improve the flatness of the battery cell.

[0009] In some embodiments of the present application, the second thickness is less than 65% of the first thickness.

[0010] In some embodiments of the present application, the first thickness is 5 to 15 μm.

[0011] In some embodiments of the present application, the first metal layer forms a first recess inward at a set position, and the second metal layer forms a second recess inward at a set position.

[0012] In some embodiments of the present application, the first metal layer, the second metal layer and the tab are connected as one at the recess.

[0013] In some embodiments of the present application, the depth of the recess is not less than the thickness of the tab.

[0014] In some embodiments of the present application, the polymer layer further includes a non-heat shrinkable material portion adjacent to the heat shrinkable material portion.

[0015] In some embodiments of the present application, the heat shrinkable material portion is a PE-EVA heat shrinkable material.

[0016] In some embodiments of the present application, the width of the heat shrinkable material portion is 2 to 5 times the width of the tab.

[0017] In some embodiments of the present application, the first metal layer and the second metal layer are independently aluminum foil or copper foil.

[0018] A second aspect of the present application provides a secondary battery, comprising any one of the aforementioned pole pieces.

[0019] According to a third aspect of the present application, there is provided an electrical device, the electrical device comprising any one of the aforementioned secondary batteries.

[0020] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a side view of the local structure of a pole piece in the prior art.

[0022] Figure 2 It is a side view of the local structure of a pole piece in one embodiment of the present application.

[0023] Figure 3 It is a side view of the local structure of a pole piece in another embodiment of the present application.

[0024] Figure 4 It is a side view of the partial structure of a pole piece in another new embodiment of the present application.

[0025] Reference numerals: first metal layer 100 , first recess 110 , polymer layer 200 , second metal layer 300 , second recess 310 , tab 400 , heat shrinkable material portion 500 , non-heat shrinkable material portion 600 . DETAILED DESCRIPTION

[0026] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.

[0027] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.

[0028] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0029] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0030] refer to Figure 1, which is a local structure of a conventional type of pole piece in the prior art. This pole piece includes a composite current collector, an active material layer (not shown in the figure) and a pole ear 400 connected to the composite current collector. The composite current collector includes a first metal layer 100, a polymer layer 200 and a second metal layer 300 arranged in sequence. The polymer layer 200 has a set thickness t1, and usually selects polyimide (PI), polyethylene terephthalate (PET) or polypropylene (PP). The first metal layer 100 is formed on one side of the polymer layer 200, and the second metal layer 300 is formed on the other side by any method including but not limited to magnetron sputtering, evaporation, water electroplating, etc. The first metal layer 100 and the second metal layer 300 can be conductive layers formed of at least one metal such as copper and aluminum. Among them, the thickness of the polymer layer 200 is usually 5 to 15 μm, and the thickness of the first metal layer 100 and the second metal layer 300 is about 1 μm. The tab 400 is divided into a negative tab and a positive tab according to the type of connected pole piece. The positive tab is usually made of aluminum, and the negative tab is usually made of nickel or nickel-plated copper, but other materials known in the art may also be used. The tab 400 is connected to a set position on the current collector (for example, a position where the active material layer is not coated in the gap in the middle of the current collector or at least one side of the edge) by means such as welding. However, in the production process of the pole piece, when welding the tab 400, the first metal layer 100 and the second metal layer 300 in the composite current collector are very thin, and it is easy to cause welding failure and failure to weld the tab. Even if the welding is successful, the welding strength of the tab 400 on the pole piece is poor, which affects the battery performance.

[0031] To this end, the present application embodiment specifically proposes a new type of pole piece structure, referring to Figure 2 The composite current collector of the pole piece includes a first metal layer 100, a polymer layer (also called an intermediate layer) and a second metal layer 300 arranged in sequence in the thickness direction. Among them, the polymer layer includes a heat shrinkable material part 500, and the heat shrinkable material part 500 usually has a first thickness t1, but is thinned relative to the first thickness t1 at the set position where the pole lug 400 is connected, so that the final thickness at the set position is the second thickness t2, so that the first metal layer 100 and / or the second metal layer 300 are recessed inwardly (that is, in the direction close to the heat shrinkable material part 500) at the set position. Specifically, the first metal layer 100 may form a first depression 110 inwardly (i.e., in a direction close to the heat shrink material portion 500 or the second metal layer 300) at the set position, the second metal layer 300 may form a second depression 310 inwardly (i.e., in a direction close to the heat shrink material portion 500 or the first metal layer 100) at the set position, or the first metal layer 100 may form the first depression 110 while the second metal layer 300 may form the second depression 310. In this case, the pole tab 400 is connected to the depression of the first metal layer 100 or the second metal layer 300 of the pole piece.

[0032] Compared with the existing conventional electrode sheets that are connected to the electrode ears when the current collector is flat, the electrode sheets provided in the embodiments of the present application make the intermediate layer on the current collector thinner at the position where the electrode ears are connected to form a depression in the metal layer, so that the metal layer of the composite current collector can be welded to the electrode ears during connection, especially welding, which can ensure the strength of the welded electrode ears and the conduction rate of electrons on the metal layer. At the same time, the electrode ears produce a structure similar to the "embedded" electrode ears on the electrode sheets, which can effectively reduce the overall thickness of the battery cell and improve the flatness of the battery cell.

[0033] Among them, the heat shrinkable material part refers to the part made of raw materials including heat shrinkable materials, and the heat shrinkable material is a smart polymer material with shape memory effect. The principle of the formation of heat shrinkable materials is that when the temperature of the cross-linked polymer reaches above the melting point, the cross-linked polymer with the crystalline phase as the reversible phase partially softens, and the fixed phase is stretched and oriented under the external force. In the subsequent rapid cooling process, the reversible phase crystallizes again, thereby freezing the tensile stress state of the fixed phase. When it is heated to the recovery temperature, the reversible phase melts and thaws, and the tensile stress is released, which is manifested as thermal contraction in the macroscopic sense. The embodiment of the present application is based on this principle. The heat shrinkable material is in an expanded state when it is below the recovery temperature, and when a recovery temperature not lower than the heat shrinkable material is applied by welding (in some cases, it also includes applying a certain pressure), the heat shrinkable material layer that was originally in an expanded state undergoes thermal contraction at the welding pole ear position and becomes thinner.

[0034] In some embodiments, the recovery temperature of the heat shrinkable material is 150-180°C, for example, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, or 180°C.

[0035] In some embodiments, the cross-linked raw materials of the heat shrinkable material include polyethylene (PE) and ethylene-vinyl acetate copolymer (EVA), and the heat shrinkable material is obtained by cross-linking reaction of these cross-linked raw materials, so that the heat shrinkable material layer formed is a PE-EVA heat shrinkable material layer. In some specific embodiments, polyethylene includes at least one of high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), etc. In some specific embodiments, the heat shrinkable material is cross-linked by raw materials including high-density polyethylene (HDPE) and ethylene-vinyl acetate copolymer (EVA), so that the heat shrinkable material layer formed is a HDPE-EVA heat shrinkable material layer. In some specific embodiments, the mass ratio of PE to EVA in the heat shrinkable material is 1 to 4:1, for example, it can be 1:1, 6.5:5.5, 7:5.5, 8.5:5, 7:4, 2:1, 7:3, 3:1, 8:2.5, 4:1. In some specific embodiments, the mass ratio of HDPE to EVA in the heat shrinkable material is 1 to 4:1, for example, 1:1, 6.5:5.5, 7:5.5, 8.5:5, 7:4, 2:1, 7:3, 3:1, 8:2.5, 4:1. In some specific embodiments, the mass ratio of HDPE to EVA is 2 to 3:1, which ensures that the heat shrinkable material has a sufficient shrinkage rate while taking into account the strength and hardness of the material.

[0036] In some embodiments, the preparation process of the heat shrinkable material includes the steps of mixing, molding, cross-linking, heating, cooling, etc. It is understandable that the above steps can be carried out in sequence, but are not limited thereto. For example, the cross-linking step can be carried out before heating and cooling, and can also be carried out after heating and cooling. In some specific embodiments, the cross-linking method includes at least one of chemical cross-linking and radiation cross-linking, that is, chemical cross-linking, radiation cross-linking, and chemical cross-linking + radiation cross-linking can be used. In some specific embodiments, when cross-linking includes the step of chemical cross-linking, the raw materials for preparing the heat shrinkable material include, in addition to the cross-linking raw materials of polyethylene and ethylene-vinyl acetate copolymer, a cross-linking agent, and a specific cross-linking agent includes, but is not limited to, at least one of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, silane cross-linking agent, epoxy cross-linking agent (such as ADR-4370F, TGIC), and anhydride cross-linking agent (such as pyromellitic anhydride). In some specific embodiments, the cross-linking agent is less than 3wt% of the cross-linking raw material, such as 2.5%, 2%, 1.5%, 1%, 0.5%, 0.2%, 0.1%. In some specific embodiments, when cross-linking includes the step of radiation cross-linking, the dose of radiation cross-linking is 30-150KGy, such as 30KGy, 35KGy, 40KGy, 45KGy, 50KGy, 55KGy, 60KGy, 65KGy, 70KGy, 75KGy, 80KGy, 85KGy, 90KGy, 95KGy, 100KGy, 105KGy, 110KGy, 115KGy, 120KGy, 125KGy, 130KGy, 135KGy, 140KGy, 145KGy, 150KGy. In some specific embodiments, the radiation cross-linking is performed by electron accelerator irradiation. In some specific embodiments, the first thickness of the heat shrinkable material layer is 5 to 15 μm, and when the radiation cross-linking is performed by 60 to 110 KGy, the shrinkage rate of the heat shrinkable material layer at the concave portion can reach 40 to 70%, and the high shrinkage of the material can ensure that it is sufficiently thin and ductile during welding.

[0037] In some embodiments, the raw material of the heat shrinkable material portion further includes an antioxidant, including but not limited to at least one of antioxidant 168, antioxidant 616, antioxidant 1010, antioxidant 1098, etc. In some specific embodiments, the amount of the antioxidant is less than 3 wt % of the cross-linking raw material, such as 2.5%, 2%, 1.5%, 1%, 0.5%, 0.2%, 0.1%.

[0038] In some embodiments, during the preparation of the heat shrinkable material, the mixing step includes mixing at 140-170°C for 5-20 minutes. The mixing temperature may be, for example, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, and the mixing time may be, for example, 5 minutes, 6 minutes, 8 minutes, 10 minutes, 12 minutes, 14 minutes, 16 minutes, 18 minutes, 20 minutes. In some specific embodiments, after mixing, the mixing step includes standing for sufficient reaction, and the specific standing time may be, for example, 8-48 hours, for example, 8 hours, 12 hours, 16 hours, 20 hours, 24 hours, 28 hours, 32 hours, 36 hours, 40 hours, 44 hours, 48 ​​hours.

[0039] In some embodiments, during the preparation of the heat shrinkable material, the heating temperature is near the recovery temperature of the heat shrinkable material, for example, it can also be 150-180°C, such as 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, etc. In some specific embodiments, the heating is performed by hot pressing, and the pressure of the hot pressing is 5-15Mpa, for example, it can be 5Mpa, 6Mpa, 7Mpa, 8Mpa, 9Mpa, 10Mpa, 11Mpa, 12Mpa, 13Mpa, 14Mpa, 15Mpa. In some specific embodiments, during the preparation of the heat shrinkable material, the cooling is cooling to room temperature (25±5°C).

[0040] In some embodiments, the second thickness t2 is less than 65% of the first thickness t1, for example, it can be 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, 0%. It is understandable that, through different heat shrinkable materials, different cross-linking methods and other processing steps, the heat shrinkable material layer can be shrunk to different degrees and thus achieve different levels of thinning in thickness, so that the second thickness t2 is controlled at a specific proportion of the first thickness t1.

[0041] In some embodiments, the heat shrinkable material layer is mixed with heat shrinkable raw materials, cross-linking agents, and antioxidants in a mass ratio of 100: (0-3): (0-3), kneaded at 140-170°C for 5-20 minutes, left to stand for 8-48 hours, hot-pressed at 150-180°C at a pressure of 5-15Mpa, cooled to room temperature, and irradiated at 30-150KGy to obtain the original heat shrinkable material part. The heat shrinkable raw materials include PE and EVA in a mass ratio of 1-4:1. When the original heat shrinkable material layer is welded to the pole ear, the heat of the welding head causes the original heat shrinkable material layer to shrink at the welding position, thereby reducing the thickness, and forming corresponding depressions on the first metal layer and / or the second metal layer to facilitate the welding and "embedding" of the pole ear.

[0042] In some embodiments, the first thickness t1 of the heat shrinkable material portion is 5-15 μm, for example, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, or 15 μm.

[0043] In some embodiments, the shape of the recess includes but is not limited to a trapezoid, a rounded trapezoid, a rectangle, a rounded rectangle or other regular or irregular shapes.

[0044] In some embodiments, the first recess 110 formed by the first metal layer 100 and the second recess 310 formed by the second metal layer 300 may be the same or different. The same means that the first recess 110 and the second recess 310 are the same in shape, size, etc. In some specific embodiments, the depth h1 of the first recess 110 and the depth h2 of the second recess 310 are similar or the same.

[0045] In some embodiments, reference Figure 3 , the first metal layer 100, the second metal layer 300 and the pole tab 400 are connected as a whole at the depression. In some specific embodiments, the first metal layer 100 forms a first depression 110, the second metal layer 300 forms a second depression 310, and the first depression 110, the second depression 310 and the pole tab 400 are connected as a whole. In some specific embodiments, the first metal layer 100, the second metal layer 300 and the pole tab 400 are welded as a whole at the depression, specifically, the first depression 110, the second depression 310 and the pole tab 400 are welded as a whole. The first depression of the first metal layer, the second depression of the second metal layer and the pole tab are in contact and connected as a whole during welding, thereby ensuring the strength of the welded pole tab to a greater extent while improving the conduction rate of electrons on the current collector.

[0046] By controlling the relative relationship between the depth of the depression and the thickness of the pole ear, the pole ear can be semi-embedded or fully embedded in the depression to be compounded with the metal layer on the current collector, so that the pole piece and the battery cell made by winding or laminating the pole piece have higher flatness and lower thickness. In some embodiments, the depth of the depression is not less than the thickness of the pole ear. Figure 3 Taking the first depression 110 as an example, the depth h1 of the first depression 110 is not less than the thickness t3 of the pole tab 400. The pole piece obtained in this way can further improve the flatness of the battery cell and reduce its thickness.

[0047] In some embodiments, reference Figure 4 , the polymer layer also includes a non-heat shrinkable material portion 600 adjacent to the heat shrinkable material portion 500. Adjacent means adjacent to the heat shrinkable material portion 500 on a plane perpendicular to the thickness direction of the pole piece, that is, adjacent to the heat shrinkable material portion 500 in the length and / or width direction of the pole piece. The non-heat shrinkable material portion means that the portion is made of raw materials including non-heat shrinkable materials. Non-heat shrinkable materials are other common polymer materials other than heat shrinkable materials, such as polymer materials commonly used in the middle layer of the pole piece in the prior art, such as at least one of polyimide (PI), polyethylene terephthalate (PET) and polypropylene (PP).

[0048] Therefore, in some specific embodiments, the polymer layer of the pole piece is entirely composed of heat shrinkable material parts, so the polymer layer can also be called a heat shrinkable material layer; and in other specific embodiments, the polymer layer of the pole piece includes a non-heat shrinkable material part formed by conventional polymer materials and a heat shrinkable material part in which the conventional polymer material is replaced with a heat shrinkable material at the welding pole ear position of the pole piece. In the latter case, in some embodiments, the width w1 of the heat shrinkable material part 500 is 2 to 5 times the width w2 of the pole ear 400, for example, it can be 2, 3, 4, or 5 times. This can ensure that the heat shrinkable material part shrinks at the welding pole ear to ensure the hardness and strength of the material; it can also ensure that there is enough recessed space at the welding pole ear to maximize the "embedded" depth requirement of the pole ear.

[0049] The thickness of the non-heat shrinkable material portion is the same as or close to that of the heat shrinkable material portion. In some embodiments, the thickness of the non-heat shrinkable material portion is 5 to 15 μm, for example, 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, or 15 μm.

[0050] In some embodiments, the first metal layer and the second metal layer of the composite current collector of the positive electrode sheet and the negative electrode sheet include at least one of metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or alloy foil of the above metals), metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or alloy mesh of the above metals). In some specific embodiments, the first metal layer and the second metal layer are independently aluminum foil or copper foil. In some specific embodiments, the first metal layer and the second metal layer are aluminum foil, or the first metal layer and the second metal layer are copper foil.

[0051] An embodiment of the present application also relates to a secondary battery, which includes the aforementioned electrode.

[0052] In some embodiments, the secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet is the above-mentioned electrode sheet having a positive electrode active material layer on at least one side, and the negative electrode sheet is the above-mentioned electrode sheet having a negative electrode active material layer on at least one side. The positive electrode sheet, the separator and the negative electrode sheet are stacked or wound to obtain the final secondary battery.

[0053] In some embodiments, the secondary battery is any one of a lithium ion battery, a sodium ion battery, a potassium ion battery, a magnesium ion battery, and a calcium ion battery.

[0054] In some embodiments, the negative electrode active material of the negative electrode active material layer on the negative electrode sheet is any one of silicon material, carbon material, and silicon-carbon composite material. Among them, the carbon material includes at least one of graphite (such as natural graphite, artificial graphite), hard carbon, soft carbon, and graphene. The silicon material includes at least one of elemental silicon, silicon oxide compounds, and silicon alloys. The above-mentioned negative electrode material can be, for example, at least one of nanoscale (such as a particle size of 0.1 to 100 nm) and micron scale (such as a particle size of 0.1 to 100 μm). In some embodiments, the positive electrode active material of the positive electrode active material layer on the positive electrode sheet is at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, nickel cobalt manganese oxide, nickel cobalt aluminum oxide, and nickel manganese aluminum oxide.

[0055] In some specific embodiments, the positive (negative) electrode active material layer includes the above-mentioned positive (negative) electrode active material, and also includes at least one of a conductive agent and a binder. Conductive agents include but are not limited to conductive graphite, conductive carbon black, conductive carbon fiber and graphene. Binders include but are not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc. For example, the negative electrode material layer includes 70-99wt% of negative electrode material, 0.5-6wt% of conductive agent and 0.5-20wt% of binder. The conductive agent and binder of the positive electrode sheet can be selected from the same range as the conductive agent and binder of the negative electrode sheet and can be the same or different materials. The optional positive (negative) electrode active material layer includes 70-99wt% of positive electrode material, 0.5-6wt% of conductive agent and 0.5-20wt% of binder. The positive (negative) electrode active material, conductive agent and binder make up the positive (negative) electrode material layer.

[0056] In some of the embodiments, the electrolyte may be at least one of a solid electrolyte or an electrolyte solution.

[0057] According to a third aspect of the present application, there is provided an electrical device, the electrical device comprising any one of the aforementioned secondary batteries.

[0058] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Among them, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0059] The present application is described below in conjunction with specific embodiments.

[0060] Example 1

[0061] The present application provides a composite current collector, the preparation process of which is as follows:

[0062] (1) Preparation of intermediate layer

[0063] High-density polyethylene, ethylene-vinyl acetate copolymer, antioxidant 1010 and triallyl isocyanurate were mixed in a mass ratio of 65:55:0.5:1, added into an internal mixer after premixing, mixed at 155°C for 10 minutes, discharged, and then left to stand at room temperature for 24 hours;

[0064] After standing still, a certain amount of the sample was weighed and placed in the mold of a flat vulcanizer for hot pressing at a temperature and pressure of 165°C and 20MPa, and then cold pressed to room temperature and then ejected from the mold;

[0065] The sample after demoulding is irradiated to 55Kgy by an electron accelerator for radiation cross-linking, thereby obtaining a heat-shrinkable composite current collector material.

[0066] The prepared heat shrinkable material and a conventional PET film are connected together by hot-melt bonding to form a whole, thereby obtaining an intermediate layer of a composite current collector, wherein the width of the heat shrinkable material portion is 4 times the width of the tab in the subsequent step.

[0067] (2) Preparation of the first metal layer and the second metal layer

[0068] Aluminum is coated on both sides of the intermediate layer material by magnetron sputtering to obtain a composite aluminum foil; copper is coated on both sides of the intermediate layer material by magnetron sputtering to obtain a composite copper foil.

[0069] (3) Preparation of pole pieces

[0070] Positive electrode sheet: The positive electrode active material LiCoO2, the conductive agent acetylene black, the conductive carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are fully and evenly dispersed in an N-methylpyrrolidone solvent system in a mass ratio of 98.2:0.5:0.3:1.0, and then coated on a composite aluminum foil, and cold-pressed into strips to obtain a positive electrode sheet.

[0071] Negative electrode sheet: The negative electrode active material nano silicon, conductive agent conductive carbon black, and binder styrene butadiene rubber are fully and evenly dispersed in an N-methylpyrrolidone solvent system in a mass ratio of 97.2:0.5:2.3, and then coated on a composite copper foil, cold pressed into strips, to obtain a negative electrode sheet.

[0072] Place the aluminum tab in the gap on the positive electrode sheet where the positive electrode active material layer is not coated, and place the nickel tab in the gap on the negative electrode sheet where the negative electrode active material layer is not coated, and weld the aluminum tab to the positive electrode sheet and the nickel tab to the negative electrode sheet by ultrasonic welding at an ultrasonic frequency of 50kHz and a static pressure of 10Mpa. During the welding process, ultrasonic welding generates a high temperature greater than 165°C at the welding point, causing the heat shrinkable material portion of the middle layer on the positive electrode sheet to shrink, and at the same time, the aluminum foil layers on both sides form a depression inward at the welding point and melt, and are connected to the melted aluminum tab to complete the welding; similarly, the heat shrinkable material portion of the middle layer on the negative electrode sheet shrinks, and at the same time, the copper foil layers on both sides form a depression inward at the welding point and melt, and are connected to the melted nickel tab to complete the welding. In this way, reference Figure 4 The tab is connected to the metal layer at a depression in the metal layer at the welding position.

[0073] (4) Preparation of batteries

[0074] Diaphragm: Choose a polyethylene (PE) membrane with a ceramic coating on the surface.

[0075] Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4 to obtain a mixed organic solvent. Then, fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0076] Preparation of a full battery: The positive electrode sheet, separator, and negative electrode sheet are wound to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0077] Embodiments 2 to 7

[0078] Examples 2 to 7 refer to Table 1. On the basis of Example 1, the mass ratio of HDPE / EVA and the radiation amount used for radiation cross-linking when preparing the heat shrinkable material layer are changed to obtain different pole pieces and full batteries.

[0079] Table 1. Raw material ratios and irradiation parameters for Example 1 and Comparative Example

[0080]

[0081]

[0082] Meanwhile, Comparative Example 1 is provided, in which the pole piece is different from that of Example 1 only in that the HDPE-EVA heat shrink material layer is replaced by a PET film of equal thickness as an intermediate layer, and the other preparation steps are the same as those of Example 1. After the pole tabs are welded, the depression of the metal layer in the example does not appear on the pole piece.

[0083] The heat shrinkable material part of the middle layer obtained in the preparation process of Examples 1 to 7 and the PET film of Comparative Example 1 were respectively taken, and heat-pressed at 180° C. and 10 MPa for 5 min by a heat press machine. The volume of the heat shrinkable material of the middle layer before and after heat pressing was detected, and the shrinkage rate of the material was calculated according to the following formula:

[0084] Shrinkage rate = (volume before hot pressing - volume after hot pressing) / volume before hot pressing × 100%.

[0085] Take the pole pieces of fixed size after welding the Al pole ear in Examples 1 to 7 and Comparative Example 1 respectively, fix the pole ear and the other side of the pole piece opposite to the pole ear in the upper and lower fixing clamps of the tensile testing machine respectively, and measure the peak tensile force of the pole ear peeling off the pole piece, which is the corresponding welding tensile force.

[0086] The test results of shrinkage rate and welding tension are shown in Table 2.

[0087] Table 2. Test results

[0088] Shrinkage Welding tension (N) Example 1 35% 9.0 Example 2 40% 10.3 Example 3 50% 12.8 Example 4 55% 14.2 Example 5 60% 15.5 Example 6 70% 18.0 Example 7 90% 18.2 Comparative Example 1 0% 5.0

[0089] It can be seen from the results in the table that the middle layer of comparative example 1 does not shrink during hot pressing and welding, while the heat shrinkable material layer prepared from heat shrinkable material in embodiments 1 to 7 shrinks by 35% to 90% during hot pressing. Therefore, during welding, the heat will also cause shrinkage and thinning, so that the outer metal layer will be concave inward, and the pole ear can be welded to the pole piece in an "embedded" manner, so that the two are more firmly connected, the welding strength is higher, and the welding effect is better. In comparison, the welding tension of comparative example 1 is only 5N, and it is easy to have poor welding between the pole ear and the pole piece.

[0090] Example 8

[0091] This embodiment provides a pole piece, which is different from the embodiment 1 in that the middle layer is completely made of heat shrinkable material.

[0092] Example 9

[0093] This embodiment provides a pole piece, which is different from Embodiment 1 in that the PET film of the middle layer as the non-heat shrinkable material part is replaced by a PI film.

[0094] Example 10

[0095] This embodiment provides a pole piece, which is different from Embodiment 1 in that the PET film of the middle layer as the non-heat shrinkable material part is replaced by a PP film.

[0096] The pole pieces provided in Examples 8 to 10 were tested for shrinkage rate and welding tension using the above method. Similar to Example 1, the welding effect between the pole lug and the pole piece was good.

[0097] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

Claims

1. A pole piece, characterized in that: include: A current collector, the current collector comprising a first metal layer, a second metal layer and a polymer layer located between the first metal layer and the second metal layer, the polymer layer comprising a heat shrinkable material portion, the heat shrinkable material portion having a first thickness and a second thickness that is thinner than the first thickness at a set position, the first metal layer and / or the second metal layer forming a recess inwardly at the set position; A pole ear is connected to the recess.

2. The pole piece according to claim 1, characterized in that: The second thickness is less than 65% of the first thickness.

3. The pole piece according to any one of claims 1 to 2, characterized in that: The first thickness is 5-15 μm.

4. The pole piece according to claim 1, characterized in that: The first metal layer forms a first recess inwardly at the set position, and the second metal layer forms a second recess inwardly at the set position.

5. The pole piece according to claim 1 or 4, characterized in that: The first metal layer, the second metal layer and the tab are connected as a whole at the recess.

6. The pole piece according to claim 1, characterized in that: The depth of the recess is not less than the thickness of the tab.

7. The pole piece according to claim 1, characterized in that: The polymer layer also includes a non-heat shrinkable material portion adjacent to the heat shrinkable material portion.

8. The pole piece according to claim 1 or 7, characterized in that: The width of the heat shrinkable material portion is 2 to 5 times the width of the tab.

9. A secondary battery, characterized in that: A pole piece comprising any one of claims 1 to 8.

10. Electrical equipment, characterized in that: A secondary battery comprising the secondary battery according to claim 9.